Political ideologies and attitudes towards income inequality in the US: a critical discourse analysis of CNN and Fox News opinion articles - Puolamäki, Jenna (My University, 2016)
The topic of the thesis is media discourse about current state if income inequality in the US, and political ideologies as influences behind the discourse. The data consists of four opinion articles, two from CNN and two from Fox News. The purpose of the study was to examine how media represents income inequality as an issue, and if the attitudes conveyed are concerned or indifferent. Previous studies have indicated that the level of income is often seen as a personal responsibility, and such perspective can be linked with Republican ideology. In contrast, the Democrats typically express more concern about the consequences of inequality. CNN has been previously considered to have a Democratic bias, and Fox News has been considered to have Republican bias, which is one reason why these two news channels were chosen as the sources of the data. The study is a critical discourse analysis, and the methods applied were sociocognitive approach, which analyzes the social and cognitive factors affecting the discourse, and appraisal framework, which was applied to scrutinize the expressed attitudes more closely by identifyind specific linguistic features. The appraisal framework includes studying such features as affect, judgment and appreciation, which offer a more detailed analysis on the attitudes present in the articles. The sociocognitive approach, additionally, offers a way of analyzing a more broad context affecting the articles. The findings were then compared, to see if there are differences between the articles, or between the news sites with alleged bias. The findings showed that CNN, with alleged Democratic bias, had a more symphatetic attitude towards income inequality, whereas Fox News, with more Republican views, showed clearly less concern towards the issue. Moreover, the Fox News articles had such dubious claims that the underlying ideology behind the articles could be even supporting of income inequality, as it allows the rich to pursue all the wealth they can without having to give anything away. The results, thus, suggest that the political ideologies may a significant effect on media discourse, which, in turn, may have a significant effect on the attitudes of the public towards great issues that could require prompt measures.